Taking mediated stance via news headline transediting: a case study of the China-U.S. trade conflict in 2018 - Qin, Binjian; Zhang, Meifang (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
This article studies mediated stance in the transedited news headlines on the 2018 China-U.S. trade conflict. It draws on Appraisal theory developed by Martin and White (2005) to examine the transeditor’s stance via an analysis of 66 English news headlines and 50 Chinese headlines. The English texts were collected from the American mainstream media, while the Chinese texts were chosen from China’s major presses. The result of the analysis shows that when news headlines are transedited from English to Chinese, stance mediation normally sounds negative towards the U.S. and positive towards China. The investigations also found that the selected Chinese presses predominantly showed heteroglossic patterns in the mediated stance they took while the English media tended to use monoglossic ones. It is argued that possible reasons for such stance deviation may include ideological tendencies of the media, different readerships and their expectations of the American and Chinese media, and the different socio-cultural beliefs between the two countries.